Physical and sensory characteristics of sourdough bread with local superfood leaf flour substitution - Rahardjo, Monika; Sihombing, Monang (Fakultas Pertanian Universitas Yudharta Pasuruan, 2026)
Introduction: Sourdough bread has gained popularity due to its nutritional and sensory benefits, with lactic acid bacteria fermentation improving digestibility, glycemic response, and bioactive compound availability. The incorporation of nutrient-dense superfood leaf flours such as Moringa oleifera, Sauropus androgynus, and Centella asiatica may further enhance its functional properties. Methods: Sourdough bread was formulated with wheat flour partially substituted by superfood leaf flours at 5%, 10%, and 15% levels. Physical properties were analyzed using a Texture Analyzer (hardness, cohesiveness, springiness, chewiness, stiffness, etc.), while sensory acceptability (appearance, aroma, taste, texture, and overall preference) was evaluated by 50 untrained panelists. Data were statistically analyzed using ANOVA and Duncan’s Multiple Range Test (α = 5%). Results: Textural analysis showed significant differences across treatments, particularly in hardness, cohesiveness, springiness, chewiness, and stiffness. Higher substitution levels of leaf flour generally increased crumb hardness and chewiness due to reduced gluten structure. Sensory analysis indicated that the control bread (100% wheat flour) received the highest overall rating. Among the modified breads, the 5% Centella asiatica formulation (TP1) was the most preferred, likely because moderate substitution imparted a mild herbal flavor and retained a soft crumb structure, while higher levels reduced sensory acceptability. Conclusion: The incorporation of superfood leaf flours significantly influenced both physical and sensory characteristics of sourdough bread. While control bread was most preferred, 5% Centella asiatica substitution emerged as the optimal formulation among the enriched variants, balancing improved nutritional potential with favorable consumer acceptance.